عولمة الخطاب المسرحي في خدمة العبور والتفهم الثقافي: قراء جديدة في مسرحية بيكت "انتظار غودو" (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
This article aims at examining the elements, goals and strategy of the absurd theatre, which helped universalize the dramatic discourse. Traditionally, aspects of drama, including setting, plot, technique, characters and themes were designed to address certain rules and regulations set up conventionally by classical dramatists, such as Plato, Aristotle, Horace, Longinus and Sidney, and attend to a certain category of people, like the upper/noble classes, in the case of the Greek and Elizabethan theatres, and the middle and lower classes in the Victorian theatre. The absurd theatre, seemingly, came as a reaction to this type of conventional drama. It is an attempt to wrestle the dramatic discourse free from the restrictions and limitations imposed upon it by the conventional rules of writing; violating the traditional rules of writing that includes language, characters, setting, theme, and technique. Herein lies the importance of this study that throws light on the dramatic discourse, which absurdists, including Beckett, attempt to globalize, following the example of the existentialism of Albert Camus and Jean Paul Sartre, who argued: "Humanity had to resign itself to recognizing that a fully satisfying rational explanation of the universe was beyond its reach", and, "the world must ultimately be seen as absurd." يهدف البحث لدراسة مسرح العبث بمقوماته، وأسسه، وأهدافه، واستراتيجيته التي تقوم على الخروج من إطار الخطاب المسرحي المبرمج، ضمن إطار محدد، للوصول إلى أكبر عدد ممكن من الناس، بمختلف جنسياتهم ومشاربهم. كما تبين الدراسة الآليات التي يلجأ إليها رواد هذا المسرح للخروج عن النص المسرحي التقليدي المعروف بأدواته المسرحية، من حبكة، وأسلوب، وتقنيات، وأفكار، ومكان وزمان الحدث المسرحي، إلى فضاء رحب تكون فيه هذه الأدوات ناظمة لعمل مسرحي يختلف بمواصفاته، ومقوماته، وأهدافه عن الأعمال التقليدية على اختلاف أنواعها، أعني تلك الأنماط المسرحية التي تقع ضمن دائرة الكلاسيكية، أو الكلاسيكية الجديدة أو الرومانسية، أو الانطباعية، أو السريالية ... الخ، ليخرج بمفردات جديدة تجعله يختلف، في قليل أو كثير، عما سبقه، أو عما جاء بعده. وتخلص الدراسة لإظهار الجانب الأبرز في هذا المسرح الذي يتلخص في توجهه نحو عولمة الخطاب المسرحي ذاته، وجعله أكثر شمولية وانفتاحاً، وقابلية لمخاطبة الآخرين، مهما كانت خلفياتهم وهوياتهم، وذلك من خلال التفرد بلغة مسرحية مرنة تخلو من القيود والضوابط،  والأطر والشكليات التي تحد من شموليته ومرونته. ومن هنا يأتي هذا البحث ليبرز ميزات مسرح العبث وأهدافه، ذلك المسرح الذي شغل حيزاً مهماً في حركة المسرح العالمية، ولعب دوراً بارزاً كمعبر ثقافي للأمم الأخرى، وصلة الوصل بين مختلف الثقافات.